Impact of posterior septectomy on olfaction in endoscopic endonasal transsphenoidal surgery - Jae Yoon Lee; Jae Sung Park; Sin Soo Jeun; Sung Won Kim; Do Hyun Kim; Soo Whan Kim (PLoS ONE, 2025)
Background Endoscopic endonasal transsphenoidal surgery is widely used to resect pituitary adenomas, yet its impact on olfactory function after resection of the posterosuperior nasal septum remains a concern. To optimize surgical techniques to preserve olfactory function, it is essential to understand the relationship between the extent of septal resection and olfactory outcomes. Methods This retrospective study analyzed 295 patients who underwent pituitary adenoma surgery. The extent of nasal septum resection was quantified and its impact on olfactory function was assessed using the Cross-Cultural Smell Identification Test (CCSIT), Sino-Nasal Outcome Test-22 (SNOT-22), and a Visual Analog Scale (VAS) for olfactory loss. Preoperative and 6-month postoperative scores were compared to evaluate changes in olfactory function. Results There was a significant correlation between larger septal resections and greater reductions in CCSIT scores, indicating a decline in olfactory function. Furthermore, patients with more extensive septal resections reported increased discomfort and olfactory loss, as evidenced by higher SNOT-22 and VAS scores. These findings highlight the importance of the nasal septum in maintaining laminar airflow and its role in olfactory function. Conclusion Study underscores the adverse effects of extensive posterior septectomy on olfactory outcomes. Minimizing the extent of septal resection may help preserve olfactory function, suggesting a need for surgical strategies that maintain septum integrity to reduce the risk of postoperative olfactory impairment.